2019
DOI: 10.1152/ajprenal.00217.2019
|View full text |Cite
|
Sign up to set email alerts
|

Role of the glucocorticoid receptor in glomerular disease

Abstract: Glucocorticoids are potent anti-inflammatory agents that are commonly used in the treatment of various glomerular diseases. Data from in vitro and in vivo studies, in both animals and humans, convincingly demonstrate that glucocorticoids have many beneficial direct effects on glomeruli, including podocytes, suggesting that, in theory, systemic administration is not necessary to achieve therapeutic benefit. Indeed, it is increasingly recognized that systemic steroids often have an unfavorable risk-to-benefit ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, the oral or intravenous use of glucocorticoids had severe side effects and gradually increased with the focus on locally targeted drugs. In vivo and in vitro studies have shown that glucocorticoids have direct renal effects, which might protect podocytes from injuries by regulating multiple podocyte-speci c targets, including nephrin, Rac1, RhoA, and actinin, while conditional knockout of the glucocorticoid receptor (GR) gene of podocytes makes mice more vulnerable to lipopolysaccharide (LPS) [23][24][25]. Colombo et al developed a nanoparticle for targeting and enriching dexamethasone into glomeruli to repair podocytes [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the oral or intravenous use of glucocorticoids had severe side effects and gradually increased with the focus on locally targeted drugs. In vivo and in vitro studies have shown that glucocorticoids have direct renal effects, which might protect podocytes from injuries by regulating multiple podocyte-speci c targets, including nephrin, Rac1, RhoA, and actinin, while conditional knockout of the glucocorticoid receptor (GR) gene of podocytes makes mice more vulnerable to lipopolysaccharide (LPS) [23][24][25]. Colombo et al developed a nanoparticle for targeting and enriching dexamethasone into glomeruli to repair podocytes [26].…”
Section: Discussionmentioning
confidence: 99%
“…The dose-dependent nature of glucocorticoids can produce serious side effects (osteoporosis, concentric obesity, infection, etc.) in clinical applications of treatment for renal inflammation [ 145 , 146 ]; therefore, Tang et al used macrophage-derived MVs delivered with dexamethasone (DEX) to treat renal inflammation and demonstrated superior ability to suppress renal inflammation compared to DEX treatment alone, without obvious adverse effects. LFA-1 and VLA-4 present on MV-DEX were responsible for their homing to the inflamed kidney.…”
Section: Application Of Cmnps In Tackling Urological Diseasesmentioning
confidence: 99%
“…Novel studies unravel a more complex relationship. For example, GCs protect podocytes through stabilisation of the slit diaphragm and cytoskeleton and preserve podocyte differentiation after injury [44]. Moreover, mice with GR knockout in podocytes are more vulnerable to kidney injury by various factors and show worse proteinuria and podocyte foot process effacement.…”
Section: Role Of Endothelial Glucocorticoid Receptor In the Pathogene...mentioning
confidence: 99%